2022
DOI: 10.1186/s40850-022-00155-4
|View full text |Cite
|
Sign up to set email alerts
|

The ontogenic gonadal transcriptomes provide insights into sex change in the ricefield eel Monopterus albus

Abstract: Background The ricefield eel is a freshwater protogynous hermaphrodite fish and has become an important aquaculture species in China. The sex change of ricefield eel is impeding its aquaculture practice, particularly the large-scale artificial breeding. Many studies including transcriptomes of mixed gonadal samples from different individuals have been aimed to elucidate mechanisms underlying the sex change. However, the key physiological factors involved in the initiation of sex change remain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…As reported, ddx6 (probable ATP-dependent RNA helicase DDX6) belongs to a family of DEAD-box RNA helicases that was highly expressed during various stages of gonad development in the Chinese mitten crab ( Eriocheir sinensis ) ( Li et al, 2015 ). Based on the ontogenic gonadal transcriptomes, the mechanisms of sex change of the ricefield eel ( Monopterus albus ) have been elucidated ( Fan et al, 2022 ), and the expression of apoeb (apolipoprotein Eb) detected was dramatically increased and peaked at the early intersexual stage. Another study has suggested that the expression of apoeb was significantly different between old and young female brains in zebrafish ( Danio rerio ) ( Zhai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, ddx6 (probable ATP-dependent RNA helicase DDX6) belongs to a family of DEAD-box RNA helicases that was highly expressed during various stages of gonad development in the Chinese mitten crab ( Eriocheir sinensis ) ( Li et al, 2015 ). Based on the ontogenic gonadal transcriptomes, the mechanisms of sex change of the ricefield eel ( Monopterus albus ) have been elucidated ( Fan et al, 2022 ), and the expression of apoeb (apolipoprotein Eb) detected was dramatically increased and peaked at the early intersexual stage. Another study has suggested that the expression of apoeb was significantly different between old and young female brains in zebrafish ( Danio rerio ) ( Zhai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through this meta-analysis, we successfully identified sex-related factors including cyp19a1a , foxl2a , hsd17b1 , amh , and gsdf , that had been previously reported to play a role in sex change in various protogynous fish species 10,14,17,19 . Furthermore, our enrichment analysis of downregulated factors highlighted a term related to the “regulation of steroid hormone production.” This finding connects to those of previous reports, which indicate that a rapid decrease in estrogen levels is crucial for female-to-male sex change 6,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that these factors are involved in gonadal transformation, particularly during the initiation of sex changes [16,19]. However, verifying their direct involvement in the sex change process remains challenging.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations